1994
DOI: 10.1021/bi00205a007
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of amino acid residue 208 in the hydrophobic binding site to the catalytic mechanism of human glutathione transferase A1-1

Abstract: Glutathione transferases (GSTs) catalyze the nucleophilic attack of the thiolate of glutathione on a variety of noxious, often hydrophobic, electrophiles. The interactions responsible for the binding of glutathione have been deduced in great detail from the 3-dimensional structures that have been solved for three different GSTs, each a member of a distinct structural class. However, the interactions of the electrophilic substrates with these enzymes are still largely unexplored. The contribution of the active-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 40 publications
4
31
0
Order By: Relevance
“…This is consistent with the binding of GSH not being significantly influenced by the Cterminal region (12,16,17,52,53).…”
Section: Asp-209 the N-cap Residue Of Helix 9 -supporting
confidence: 88%
See 2 more Smart Citations
“…This is consistent with the binding of GSH not being significantly influenced by the Cterminal region (12,16,17,52,53).…”
Section: Asp-209 the N-cap Residue Of Helix 9 -supporting
confidence: 88%
“…It would appear that the reduction in catalytic efficiency is not due to an increase in K m CDNB but rather a decrease in k cat CDNB (not determined). A decrease in k cat CDNB , in turn, would not be due to a decreased rate of product release, because mobility-enhancing perturbations in the Cterminal region generally increase the rate of product release (12,51,53). Rather, it is most likely that the affinity of the H-site for CDNB is reduced, which is consistent with the link between productive binding of CDNB and the dynamics of the C-terminal region (9).…”
Section: Asp-209 the N-cap Residue Of Helix 9 -mentioning
confidence: 74%
See 1 more Smart Citation
“…44 X-ray crystallographic studies have also suggested that Tyr 108 in hGST P1-1 is located at the substrate-binding site and it is in a structurally conserved position within the mu, pi and theta classes, and appears to be one of the few polar residues contributing to the H-site. [27][28][29][30][31][32] In order to elucidate the precise enzyme-substrate interactions responsible for the catalytic properties of GST, the mutant enzymes of Tyr 108 residue in hGST P1-1 were expressed in E. coli, purified to electrophoretic homogeneity by affinity column chromatography and examined the enzymatic properties of the mutated enzymes. The substitutions of Tyr 108 with alanine, phenylalanine and tryptophan greatly affected the catalytic properties of hGST P1-1 toward a number of substrates, as discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent crystallographic studies of all five GST classes show that the H-site is quite different among them and very little is known about the key determinants of xenobiotic substrate specificity. 10,11,[24][25][26][27] Only a few amino acid residues have been identified as key determinants of the H-site : Tyr 115 in rat mu GST (isoenzymes 3-3 and 4-4), 28,29 Met 208 in GST A1-1, 30 Ile 104 in GST P1-1, 31 and Val 10, Arg 11, and Val 104 in the murine class pi GST. 32 Previously, we reported the importance of Tyr 108 for the binding of the electrophilic substrate of hGST P1-1.…”
Section: Introductionmentioning
confidence: 99%